Short courses of ofloxacin for the treatment of enteric fever. - Nguyen, T; Solomon, T; Mai, X; Nguyen, T; Nguyen, T; Wain, J; To, S; Smith, MD; Day, N; Le, T; Parry, C; White, N (1997)
Typhoid fever continues to be a major public health problem in tropical countries, exacerbated in recent years by the spread of multi-drug resistant strains of Salmonella typhi. Short treatment courses of fluoroquinolones are effective, and have the advantage of reduced cost and increased compliance, but the optimal length of treatment is unknown. In an open, randomized comparison, 107 adults with uncomplicated enteric fever (95 of whom had positive blood cultures for S. typhi and 5 for S. paratyphi) were treated with oral ofloxacin, 15 mg/kg/d for 2 d or 10 mg/kg/d for 3 d. Mean fever clearance times were the same in the 2 treatment groups (97 h). There were 7 treatment failures, one in the 2 d group and 6 in the 3 d group (P = 0.07). Three of the 5 patients infected with nalidixic acid resistant strains of S. typhi had treatment failures, compared with 4 of 90 with nalidixic acid sensitive isolates (P < 0.0001; relative risk 13.5, 95% confidence interval 4.1-43%). Treatment with ofloxacin for 2 or 3 d is equally effective in adults with uncomplicated enteric fever caused by nalidixic acid sensitive strains of S. typhi. The epidemiology and management of nalidixic acid resistent typhoid needs further investigation.